THE IMPACT OF FUEL SUBSIDY REMOVAL ON CONSUMER GOODS IN SELECTED STATES IN NIGERIA - Okwa, F. O.; Okwonu, F. Z.; Owoyi, Mildred C. (FUDMA Journal of Sciences, 2024)
Fuel subsidy removal in Nigeria has impacted consumer goods, transportation, and house rent in different facets. Political economists and data analysts opined that fuel subsidy removal frees up resources, while others say it enhances poverty. This study was conducted to investigate the impact of fuel subsidy removal on consumer goods. The rentier state theory was employed as the theoretical framework for analysis, and the study used the descriptive survey method with a cross-sectional procedure as the research design. The study employed the frequency distribution, and simple percentages to analyze the impacts of fuel subsidy removal. The Wilcoxon signed-rank test was used to test the formulated hypotheses at a significance level of 5%. The study affirmed that the removal of fuel subsidy increased the cost of consumer goods, since factors such as house rent and transportation which generally have effect on the cost of goods are affected, leading to poor standard of living of Nigerians.